2009
DOI: 10.1111/j.1365-2982.2009.01439.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p38 MAPK improves intestinal disturbances and oxidative stress induced in a rabbit endotoxemia model

Abstract: Lipopolysaccharide decreases the duodenal contractility in rabbits and increases the production of free radicals. p38 MAPK is a mediator of these effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 49 publications
6
26
0
Order By: Relevance
“…In this study we demonstrate that blockade of p38, JNK1/2 or ERK1/2 pathways abolished the effect of LPS on the acetylcholine-induced contractions in rabbit ileum. We have shown similar results in rabbit duodenum (6,8,9) although there are some differences. The effect of LPS in the longitudinal layer is higher in the duodenum than in the ileum (58 vs. 43% of reduction), while the effect of LPS is similar in the circular layer of duodenum and ileum.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In this study we demonstrate that blockade of p38, JNK1/2 or ERK1/2 pathways abolished the effect of LPS on the acetylcholine-induced contractions in rabbit ileum. We have shown similar results in rabbit duodenum (6,8,9) although there are some differences. The effect of LPS in the longitudinal layer is higher in the duodenum than in the ileum (58 vs. 43% of reduction), while the effect of LPS is similar in the circular layer of duodenum and ileum.…”
Section: Discussionsupporting
confidence: 74%
“…In previous studies we have described a similar localization of these MAPKs in the rabbit duodenum, although the expression of p-p38 and p-ERK1/2 in the smooth muscle of duodenum was lower than in ileum (6,8,9).…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have reported high expression of phospho-p38 MAPK in neurons of rabbit duodenum (GONZALO et al, 2010). Also, it has been showed that surgical manipulation can lead to oxidative stress (ANUP et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…COX-2 is an inducible form of the enzyme produced in a variety of stress conditions, such as sepsis 4 , tumor 5 , operative manipulation 6 and bowel obstruction 7 . Recent studies indicate that inducible expression of COX-2 in endotoxemia rats induces the motility disturbance of intestine 8,9 . Conversely, suppression of COX-2 using inhibitor of mitogen activated protein kinase attenuates the intestinal dysmotility 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that inducible expression of COX-2 in endotoxemia rats induces the motility disturbance of intestine 8,9 . Conversely, suppression of COX-2 using inhibitor of mitogen activated protein kinase attenuates the intestinal dysmotility 8,9 . These findings suggest that COX-2 is associated with the development of the intestinal dysmotility induced by endotoxin.…”
Section: Introductionmentioning
confidence: 99%